Study on Mechanical Characteristics of Discontinuous Cut-Off Wall of Dam Foundation Based on Plastic Damage Calculation Method - Dinghan Fang; Kaituo Wang; Shuochang Xu; Xingchen Wang (Buildings)
Dam foundations are prone to leakage damage after being exposed to long-term water action, which seriously affects the operation safety of the dam. At present, concrete cut-off walls serve an important means of anti-seepage for dam foundations. However, due to construction challenges, the cut-off wall needs to be poured segment-by-segment during the construction process, and the joints between adjacent segments become weak parts for seepage prevention. Therefore, it is crucial to clarify the stress state of segmented discontinuous concrete cut-off walls. Based on the Lee-Fenves framework and the tension–compression constitutive relationship of fracture energy, a plastic damage calculation method was established in this paper to characterize the mechanical behavior of discontinuous cut-off walls. The method was then used to analyze the mechanical performance of discontinuous walls with segment joints containing slurry cake. The research results showed that compared to the continuous cut-off wall, the vertical settlement in the middle part of the discontinuous cut-off wall increased by 5.8%, and the displacement along the river flow direction decreased by 35.3%. As the wall segment width decreased, the joint opening and the degree of tensile damage were reduced accordingly, while the compressive damage in the middle and lower parts of the wall was intensified. As the wall depth decreased, the constraints and load on the bottom of the wall showed obvious changes, leading to a reduced stress and damage level of the wall. The findings provide reference for the design and safety control of cut-off walls.